A modified phase-coding method for absolute phase retrieval. (December 2016) - Xing, Y.; Quan, C.; Tay, C.J.
Abstract: Fringe projection technique is one of the most robust tools for three dimensional (3D) shape measurement. Various fringe projection methods have been proposed for addressing different issues in profilometry and phase-coding is one such technique employed to determine fringe orders for absolute phase retrieval. However this method is prone to fringe order error, while dealing with high-frequency fringes. This paper studies phase error introduced by system non-linearity in phase-coding and provides a mathematical model to obtain the maximum number of achievable codewords in a given scheme. In addition, a modified phase-coding method is also proposed for phase error compensation. Experimental study validates the theoretical analysis on the maximum number of achievable codewords and the performance of the modified phase-coding method is also illustrated. Highlights: Studied phase errors introduced by system non-linearity in phase-coding method. Provided a mathematical model to obtain the maximum number of achievable codewords by conventional phase-coding method. Proposed a modified phase-coding method for phase error compensation. A larger number of codewords can be employed in the proposed method without increasing the number of projected patterns. The performance of the modified phase-coding method has been demonstrated by experimental results.